La trans-formación del Derecho: La evolución del Derecho Internacional de los Derechos Humanos para proteger la identidad de género de las personas trans - Lengua Parra, Adrián (2019)
The present paper seeks to describe the process of recognition of gender identity as a prohibited reason for discrimination in International Human Rights Law (hereafter, IHRL) and show how this has allowed a better protection of the rights of trans people. For it, this document realizes a classification of the speeches that have addressed the situation of these people and their relationship with the law. On this basis, it is postulated that the IHRL have supported a model that seeks the depathologization of trans identities and it is explained which the actual protection standard that States must comply in order to protect the right of identity of that population.